Polish Liberal Thought Before 1918 - Janowski, Maciej (Central European University Press, 2022)
Based on solid research, this erudite study is a first attempt at presenting a comprehensive analysis of nineteenth-century Polish liberalism. Polish liberal tradition has generally been considered weak or even nonexistent. Janowski, on the other hand, argues that nineteenth-century Poland inherited a strong protoliberal tradition from the nobility-based democracy, and that in the mid-nineteenth century, liberalism was a dominant trend in Polish intellectual life, even if it rarely appeared in its pure form and did not create political movements separating liberal aims from patriotic ones